2007
DOI: 10.3163/1536-5050.95.2.195
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the literature of athletic training

Abstract: This paper identifies the core literature of athletic training and determines which major databases provide the most thorough intellectual access to this literature. Methods:This study collected all cited references from 2002 to 2004 of three journals widely read by those in the athletic training field. Bradford's Law of Scattering was applied to the resulting list to determine the core journal titles in the discipline. Three major databases were reviewed for extent of their coverage of these core journals.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…To date, the allied health project has given rise to fifteen mapping studies covering a diverse range of allied health disciplines [4]. As of this writing, athletic training [5] and health care management [6] are the two most recent allied health disciplines to be included in the project. The companion project covering nursingrelated fields has produced seventeen studies [7].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the allied health project has given rise to fifteen mapping studies covering a diverse range of allied health disciplines [4]. As of this writing, athletic training [5] and health care management [6] are the two most recent allied health disciplines to be included in the project. The companion project covering nursingrelated fields has produced seventeen studies [7].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a prevalence (.50%) of ATs are now employed in settings other than high schools, colleges, and professional sports (eg, hospitals, physician and physical therapy clinics, and industrial settings), perhaps guided by the opportunity to receive third-party reimbursements. 3,4 The trend toward thirdparty reimbursement in athletic training practice has contributed to an increased use of evidence-based outcomes to guide clinical approaches. 5 However, athletic training scholars are concerned that outcomes research for athletic training is ''lagging behind'' other health care professions and that increased educational rigor might be necessary to facilitate the needed investigations.…”
mentioning
confidence: 99%
“…6 Athletic training education has evolved into a more standardized and distinct academic major at the undergraduate and graduate levels, ultimately leading to an increased need for doctoral-educated ATs to fill tenure-track faculty positions. 7 Several authors 4,7 have suggested to include instruction in research methods in entry-level coursework, so that future ATs can gain the tools needed to appraise and potentially contribute to the research base. Currently, the Commission on Accreditation of Athletic Training Education indicates that statistics and research design should be included in the subject matter that constitutes the ''core'' of the AT academic curriculum.…”
mentioning
confidence: 99%
“…In 2007, one publication mapping the AT literature found 8,678 citations, with 35% of these in 6 medical journals. 54 Although there have been several calls for more evidence-based medicine and outcomes research 55,56 some of the more basic questions in athletic training have not been adequately addressed to date. One of the more fundamental questions is whether or not ATs are effective in reducing the incidence of injuries and/or returning injured athletes more quickly to the athletic field.…”
Section: Athletic Trainersmentioning
confidence: 99%